IMPROVING TEACHING USING MOBILE APPLICATIONS IN DEVELOPING THE CREATIVE ACTIVITY OF FUTURE IT TEACHERS - F.Kh. Rasulova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides extensive information about the creation of electronic educational resources based on mobile technologies, mobile education, the possibilities and conveniences of mobile education are highlighted. The analysis of world trends shows that the use of mobile technologies for solving various pedagogical tasks in the educational process is of great vital importance. The article also presents the technology of creating electronic educational resources based on mobile technologies, programs that create mobile books, and several ways of using mobile devices for educational purposes.